Islam Transnasional Versus Islam Nusantara - Achmad Luqman Habibullah; Uun Yusufa; Siti Masrohatin (The Eastasouth Journal of Social Science and Humanities, 2026)
The phenomenon of transnational Islamic movements has become a global concern because it affects the religious and social dynamics of a country. As the largest Muslim-majority country, Indonesia has become fertile ground for the spread of transnational Islamic ideologies that carry conservative and puritanical values. On the other hand, the concept of Islam Nusantara has emerged as a local response that promotes values of tolerance, culture, and the contextualization of Islamic teachings within the local culture. This study aims to identify the influence of these two currents of Islamic thought, transnational and Nusantara, in shaping the Islamic identity of Indonesian society. This study uses a qualitative research method with a descriptive-explanatory approach that compares the similarities and differences in the impact, nature, and effects of the growth of transnational Islam and Islam Nusantara movements. Data collection techniques include observation, interviews, and documentation. The research uses Mark R. Woodward's cultural Islam theory, which views Islam as a syncretic tradition embedded in local culture and wisdom. The results of the study show that transnational Islam has a very effective influence in shaping exclusive religious-based political and social movements, while Islam Nusantara is more adaptive to the local context and tends to strengthen social harmony. The infiltration of transnational movements in Indonesia has weakened traditional bases such as Nahdlatul Ulama, while Islam Nusantara is positioned as an ideological and cultural stronghold that seeks to maintain contextual Islamic moderation amid global trends.